Effects of expanding and pelleting diets on finishing pigs fed from wet/dry feeders - Amornthewaphat, N.; Hancock, Joe D.; Behnke, Keith C.; McKinney, Leland J.; Starkey, C.W.; Lee, D.J.; Jones, C.L.; Park, J.S.; Dean, D.W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pigs fed pelleted and expanded diets from wet/dry feeders had 4.4% greater ADG and 7.9 % greater efficiency of gain than pigs fed a mash diet. Also, trends for greater efficiencies of gain occurred among pigs fed expanded pellets vs standard pellets and expandate vs expanded pellets.
Keywords: Swine; Expanding; Pelleting; Wet/Dry feeders; Finishing pigs